2016
DOI: 10.1021/acs.jnatprod.5b01051
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of the Naturally Occurring Glycosylflavone Aciculatin

Abstract: The new flavone-glycoside aciculatin (1), from Chrysopogon aciculatus, has been shown to have cytotoxic, anti-inflammatory, and antiarthritis activity. Further biological studies have been limited because of the limited availability of 1 from natural sources. Herein the first total synthesis of 1 in an overall yield of 8.3% is described. The synthesis involved the regio- and stereoselective glycosylation-Fries-type O-to-C rearrangement to construct the C-aryl glycosidic linkage, followed by a Baker-Venkatarama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…As long as the glycosyl donor A is sufficiently activated by Lewis acids or other reaction promoters, this facile process proceeds even at −78 °C (typically employed in the initial studies). Thus, various glycosyl donors, including glycosyl fluorides as above, ,,, and glycosyl acetates, ,,, 1-OH sugars, methyl glycosides, ,, thioglycosides, glycosyl imidates, glycosyl phosphates, ,, and glycals, , have been used in combination with suitable activators (Scheme ).…”
Section: Methodologies For Constructing Aryl C-glycoside Linkagesmentioning
confidence: 99%
See 2 more Smart Citations
“…As long as the glycosyl donor A is sufficiently activated by Lewis acids or other reaction promoters, this facile process proceeds even at −78 °C (typically employed in the initial studies). Thus, various glycosyl donors, including glycosyl fluorides as above, ,,, and glycosyl acetates, ,,, 1-OH sugars, methyl glycosides, ,, thioglycosides, glycosyl imidates, glycosyl phosphates, ,, and glycals, , have been used in combination with suitable activators (Scheme ).…”
Section: Methodologies For Constructing Aryl C-glycoside Linkagesmentioning
confidence: 99%
“…In 2016, Lee and co-workers synthesized aciculatin (Scheme ). The initial C -glycoside bond formation was achieved by the reaction of thioglycoside 636 and phenol 623 in the presence of NIS and TfOH, giving C -glycoside 637 . A similar transformation as that stated earlier afforded aciculatin.…”
Section: Natural Product Synthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…而金催化的邻炔基 苯甲酸糖基酯法由于它们参与形成强的分子内氢键, 使 得黄酮类 5-OH 反应活性大大提高, 从而实现了黄酮 [71,72] 、抗炎 [73] 等活性, 然而其 在植物中含量极低, 从干燥的竹节草根和根茎提取分离 获得的刺果素苷产率仅为 0.26% [71] , 其化学合成受到了 化学家重视. 文献报道, 首先通过在 NIS/TfOH 酸性条 件下, 2-羟基-4,6-二甲氧基苯乙酮(64)与 α/β 构型洋地黄 毒糖糖基供体通过 Fries 型 O→C 重排反应构建 C-芳基 糖苷键, 得到关键中间体 α-羟基芳基 C-糖苷 (65), 然后 以 EDC/DMAP 介导、催化与 4-苄氧基苯甲酸进行酯化 反应, 再通过 BK-VK 重排得到 β-丙二酮中间体 (67), 以 CSA 介导环化脱水反应构建黄酮结构单元, 最后去苄 基 化 和 苯 甲 酰 基 化 合 成 了 刺 果 素 苷 (69), 总 收 率 为 8.3% [74] (Scheme 12).…”
Section: 金催化的邻炔基苯甲酸糖基酯法unclassified
“…Compound 13 was then converted into flavone 14 (89% in two steps) using a catalytic amount of concentrated HCl in AcOH at 110 °C. 10 The preliminary examination of the deprotection of 14 under a H 2 atmosphere showed that the reaction did proceed in the presence of Pd/C or Pd(OH) 2 / C, 11 but the yield of 5a from 14 is very modest (<20%) even if the reaction time was extended to 3 days. We subsequently tested the HCl/AcOH (v/v = 1/2) deprotection system, which generated the desired flavone 5a in a satisfactory yield (75%).…”
mentioning
confidence: 99%